Effects of Current Density and Deposition Time on Corrosion Behaviour of Nickel-based Alloy Coatings - Md Nor, M S; Salleh, Zuraidah; Masdek, N R N M; Kushairi, S; Abu, M Z; Omar, N J N (International Journal of Integrated Engineering, 2022)
Corrosion of fasteners is an on-going issue and stainless steel 304 (SS304) is prone to this destructive process. One method to mitigate corrosion is electrodeposition of Co-Ni-Fe nanoparticles.  This paper studied the effects of deposition time and current density on corrosion behaviour of Co-Ni-Fe coated SS304 bolt. Co-Ni-Fe ternary alloys were electrodeposited onto SS304 bolt in 15, 30, or 45 minutes by using current density of 28, 35, 42 mA/cm2. Combinations of these parameters produced 9 samples. These samples were electrochemically tested by a potentiostat using open circuit potential (OCP) and potentiodynamic polarization (PDP). The samples were also characterised in terms of surface roughness and thickness of the coatings by using 3D surface metrology system. The OCP value decreased when deposition time was increased. All sample synthesised in 30 minutes had a more stable OCP curve. PDP curves exhibited active behaviour without passivation region. The corrosion potential (Ecorr) of T15 samples was more anodic than T30 and T45 samples. The corrosion current density (Icorr) of all samples fluctuated. Sample synthesised in 30 minutes using 42 mA/cm2 had the lowest corrosion rate. It was found that the surface roughness influences the corrosion behaviour in which a lower surface roughness tends to produce coating with better corrosion performance. Current density had small effect on the thickness of coating, whereas the tendency of a thickness to increase was obvious for deposition time.